Online density meter for Liquid Desiccant Dehumidification System (LDDS) - Wang, Weiqian. (2013)
This report is the documentary of the project with title “Online density meter of liquid desiccant dehumidification system”. The liquid desiccant dehumidification system was developed for its high efficiency in removing humid and energy saving properties. In the dehumidification process, the liquid desiccant is circulating in the system. In order to achieve a better dehumidification result, the liquid desiccant needs to be control precisely. For this reason, a real time density meter needs to be developed to monitor the liquid desiccant’s density in different parts of the system.